Surgical anatomy of the feline sacroiliac joint for lag screw fixation of sacroiliac fracture-luxation - Burger, M.; Forterre, F.; Brunnberg, L. (Veterinary and Comparative Orthopaedics and Traumatology, 2004)
Twenty-eight feline pelves (56 hemipelves) were examined in order to identify the location for optimal sacroiliac screw placement in sacroiliac fracture-luxation repair. A drill hole was started on the median plane of the hemipelvis in the centre of the body of the first sacral segment until it penetrated the lateral cortex of the ilial wing, thus providing optimal drill hole placement. The position of the drill hole on the articular surface of the sacral wing and on the lateral surface of the ilial wing was measured. The distance of the drill hole from the cranial margin of the sacral wing was 51% of sacral wing length, just cranial to the crescent shaped hyaline cartilage. The distance from the dorsal margin was 47% of sacral wing height. The drill bit direction has to be adjusted to the cranio-caudal inclination (range 10° to 29°) and dorso-ventral inclination (range 2° to 25°) of the sacral wing. A notch in the cranial edge of the sacral wing was present, with variable position, in 34% of the specimens and is consequently not a useful landmark for sacroiliac screw placement. The drill hole on the lateral surface of the ilium was located in craniocaudal direction at a distance of 69% of sacral tuber length, measured from the cranial dorsal iliac spine. The dorso-ventral position of the drill hole was at a distance of 52% of ilial wing height measured from the sacral tuber. The ventral gluteal line, present in 93% of the cases, is a useful landmark to locate optimal screw hole position on the ilial wing.
Keywords: Sacroiliac joint; anatomy; feline; fracture-luxation; lag screw fixation